1999
DOI: 10.2105/ajph.89.5.731
|View full text |Cite
|
Sign up to set email alerts
|

Minor tobacco alkaloids as biomarkers for tobacco use: comparison of users of cigarettes, smokeless tobacco, cigars, and pipes.

Abstract: OBJECTIVES: This study (1) determined levels of various tobacco alkaloids in commercial tobacco products. (2) determined urinary concentrations, urinary excretion, and half-lives of the alkaloids in humans; and (3) examined the possibility that urine concentrations of nicotine-related alkaloids can be used as biomarkers of tobacco use. METHODS: Nicotine intake from various tobacco products was determined through pharmacokinetic techniques. Correlations of nicotine intake with urinary excretion and concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
120
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(126 citation statements)
references
References 25 publications
5
120
0
1
Order By: Relevance
“…Some contents and designs that may increase dependence potential and/or consumer appeal may also increase toxicant exposure (23,24). For example, acetaldehyde (25), a by-product of the combustion and/or pyrolysis of simple sugars, is a known carcinogen that appears to potentiate the dependencecausing effects of nicotine.…”
Section: Other Contentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some contents and designs that may increase dependence potential and/or consumer appeal may also increase toxicant exposure (23,24). For example, acetaldehyde (25), a by-product of the combustion and/or pyrolysis of simple sugars, is a known carcinogen that appears to potentiate the dependencecausing effects of nicotine.…”
Section: Other Contentsmentioning
confidence: 99%
“…cinnamaldehyde and gluco-vanillin) designed to flavour mainstream (20) and sidestream smoke (21) with a sweet, vanillin-type aroma. Additional flavour technologies described in tobacco industry documents include flavour microencapsulation in the paper, packaging technology, polymer-based flavour fibres inserted into the filter, and flavoured tipping (18,(22)(23)(24)(25)(26)(27).…”
Section: Flavour Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…1 While nicotine is the primary tobacco constituent responsible for addiction, many of the other over 8,400 identified tobacco constituents, 2 including alkaloids, flavor additives, β-carbolines, and monoamine oxidase inhibitors, may also affect use and dependence. 3 Given the sparse knowledge about the in vivo pharmacology of most of these constituents, the objective of this study was to examine the effects on locomotor activity of anatabine and myosmine (two alkaloids that are present in larger quantities in tobacco products, including e-cigarettes; Etter, Zäther, and Svensson 4 ; Jacob et al 5 ), cotinine (common tobacco constituent and a metabolite of nicotine; Jacob et al 5 ) and nicotine (for comparison purposes). Nicotine doses (0.1-0.8 mg/kg, subcutaneous [s.c.]) were chosen based upon literature review, which showed that acute doses within this range affected locomotor activity, produced discriminative stimulus effects, and increased dopamine overflow in brain reward areas (for review, see Matta et al 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Neste sentido, demonstrou-se que a nornicotina, um alcalóide constituinte do tabaco e também um metabólito ativo da nicotina (Jacob et al, 1999), induz a auto-administração em ratos (Bardo et al, 1999) e aumenta a liberação de dopamina, in vitro, em fatias de núcleo acumbens (Green. et al, 2002).…”
Section: Propriedades Reforçadoras Da Nicotinaunclassified